Avaliação do apoio social percebido por pacientes com doença renal crônica em hemodiálise e cuidadores familiares - Cruz, Tarzie Hübner da (2017)
Chronic kidney disease (CKD) is among the fastest growing health problems in the world. Because it is a silent disease, it can sometimes go unnoticed by person, which can lead to starting of dialysis treatment. So, offering support to these people is relevant, because treatment can trigger diverse needs. The objective of this study is evaluate the social support present in daily life and in the care of renal patients on hemodialysis and family caregiver. It is research with a quantitative, transversal approach. The study was attended by 220patients with chronic renal failure in hemodialysis and 16 family caregivers attended at a renal clinic during the data collection period (July to October, 2016), aged over 18 years, on hemodialysis treatment, at least , 4 months, and patients without octo and allo psychic alterations. Caregivers were more than years old, should be present the day of application of the instrument be caregiver of patient under treatment by hemodialysis. A sociodemographic and clinical instrument and the scale of the Medical Outcomes Study were applied to patient and caregivers. The data collected was typed into a spreadsheet by means of double independent typing. For the processing and confection of the database was used Microsoft Excel. The Statistical Package for Social Sciences (SPSS) software version 15.0. The Shapiro Wilk normality test was used and the significance criterion adapted was the 5%level. Student’s t test was also applied. Anova and Pearson correlation test. Ethical precepts were based on Resolution number 466/12. The sample studied was composed of 220 patients with chronical renal failure in hemodialysis, 55, 5% were male and 44, 5% female. The overall mean aged was found to be at least 23, 35 years and a maximum of 89, 41 years. In the evaluation of social support, it was found that patient with higher education, married, who know how to read, who work, with leisure activities, have grater social support. The sample of caregivers who accompany patients with renal chronic failure during the hemodialysis sessions. The majority of caregivers were female (93,8%) mean age 45.07 ((± 12,71) years, minimum. Only one of the interviewees was male, aged 37 years. Statistical significance was observed between the mean score of the material factor and the educational variable, affective score and the variable material status and leisure emotional score and the variable material status and work information score and the variable residence type and score social interaction in relation to the variable material status, type of residence and leisure. Nursing actions are necessary for this population that present lower scores of social support.